2002
DOI: 10.1051/0004-6361:20011665
|View full text |Cite
|
Sign up to set email alerts
|

SC 1327–312 & SC 1329–313: Two galaxy groups in-between a major merging event observed with Beppo–SAX

Abstract: Abstract. We present the results of two Beppo-SAX observations of the poor clusters SC 1327-312 and SC 1329-313: these objects are located in a huge structure, formed by three ACO clusters, which is probably the remnant of one of the largest and best studied major mergings known. Given the fact that these poor clusters are in between two interacting ACO clusters, the aim of this work is to study the physics of the intracluster medium and to look for the possible presence of shocks. We derived the gas distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…Note that the SC 1329 group has a bimodal velocity distribution: the optical clumps associated to the two velocity peaks are named T520 and T496 (Bardelli et al 1998a). a Bardelli et al (1998b), b Bardelli et al (1998a), c Bardelli et al (2002), d Ettori et al (2000). resembles the results of the numerical simulations carried out by Roettiger et al (1997) for the case of a collision of two clusters.…”
Section: The Cluster Merger In A3558-csupporting
confidence: 55%
“…Note that the SC 1329 group has a bimodal velocity distribution: the optical clumps associated to the two velocity peaks are named T520 and T496 (Bardelli et al 1998a). a Bardelli et al (1998b), b Bardelli et al (1998a), c Bardelli et al (2002), d Ettori et al (2000). resembles the results of the numerical simulations carried out by Roettiger et al (1997) for the case of a collision of two clusters.…”
Section: The Cluster Merger In A3558-csupporting
confidence: 55%
“…The size of the relic in our image is ∼ 350 kpc, which is small but not unusual. Its radio power is low (P 325 MHz = 3 × 10 23 W Hz −1 ), and it is at least qualitatively consistent with the scaling relation between the radio power of relics and the mass of the host cluster (see de Gasperin et al [18]), considering that the mass estimated for SC 1329-313 from Beppo-SAX observations is approximately ∼ 3.5 × 10 14 M Sun (Bardelli et al [47]). The relic is overlaid on the XMM-Newton X-ray image in Figure 4, which clearly shows the location between the two SC groups.…”
Section: The Relicsupporting
confidence: 67%
“…The presence of a radio halo in this cluster (Giacintucci et al 2005) indicates a merger activity, since radio halos have only been found in interacting systems. Evidence of interaction also comes from Beppo-SAX data (Bardelli et al 2002). Using XMM-Newton data, Finoguenov et al (2004) suggest that the SC 1329-313 group southwest of A3562 has passed to the north of A3562, and the cluster core is likely oscillating in response to the passage of the group.…”
Section: Merger Cold Frontsmentioning
confidence: 99%